ANALISIS KOMPETENSI GURU DALAM MENGAJAR PKN DI SEKOLAH DASAR - Febrianti Putri Siahaan; Khairunnisa; Yora Marsia Br S.Pandia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to investigate teachers' knowledge, skills and attitudes towards Citizenship Education (PKN) learning in elementary schools. By focusing on the effectiveness of PKN teaching, this research analyzes three main aspects: knowledge and mastery of PKN material, the effectiveness of teachers' skills in managing classes and implementing innovative learning methods, as well as teachers' attitudes towards the role of PKN in shaping student character. The research method used is a descriptive study with a quantitative and qualitative approach. Data was collected through surveys and interviews with elementary school teachers in several areas. The research results show that there are variations in teachers' knowledge, skills and attitudes towards PKN learning. Several factors such as lack of training, limited resources, and curriculum pressure influence the effectiveness of PKN teaching. The implications of these findings support the importance of increasing teacher competency and greater support from schools and the government in improving PKN learning in elementary schools. Keywords: Citizenship Education, teachers, elementary schools, knowledge, skills, attitudes